2019
DOI: 10.1002/ags3.12232
|View full text |Cite
|
Sign up to set email alerts
|

Current status of the “enhanced recovery after surgery” program in gastric cancer surgery

Abstract: Since the late 1990s, perioperative care through the enhanced recovery after surgery (ERAS, European Society for Clinical Nutrition and Metabolism [ESPEN]) program has spread. ERAS protocols aim to reduce surgical complications, improving postoperative outcomes and thereby saving resources by addressing various clinical elements through a multidisciplinary approach or based on evidence. In the field of gastric cancer, the philosophy of ERAS has gradually become accepted and, in 2014, consensus guidelines for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 51 publications
1
22
0
Order By: Relevance
“…A meta-analysis has shown that early enteral nutrition is associated with lower mortality and a shorter hospital stay after gastrectomy [26]. We observed a significantly earlier intake of liquid nutritional supplement, and a non-significantly earlier intake of soft and full diet after CP implementation.…”
Section: Discussionmentioning
confidence: 51%
“…A meta-analysis has shown that early enteral nutrition is associated with lower mortality and a shorter hospital stay after gastrectomy [26]. We observed a significantly earlier intake of liquid nutritional supplement, and a non-significantly earlier intake of soft and full diet after CP implementation.…”
Section: Discussionmentioning
confidence: 51%
“…In patients with moderate and severe malnutrition, nutritional input is required before any type of treatment, for 7-14 days, in order to reduce morbidity and mortality. Patients initially submitted only to neoadjuvant treatment, also have indication of nutritional therapy, particularly those with food intake below 70% of estimated energy spent 13 , 46 .…”
Section: Resultsmentioning
confidence: 99%
“…Based on the guidelines for enhanced recovery after surgery, [ 25 , 26 ] TPN is not recommended as a method of nutritional support after upper gastrointestinal surgery. The existing routine of nil-by-mouth for upper gastrointestinal surgery remains unchallenged.…”
Section: Discussionmentioning
confidence: 99%